Evaluation of Optimal Control Strategies for Buck Converter in Electric Vehicle Battery Applications - Kaba, B.; Öztürk, G.; Tören, M. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2025)
This study investigates a buck converter, commonly utilized with lithium-ion (Li-ion) batteries in electric vehicles (EVs), by employing three control methodologies: Proportional-Integral (PI) Control, State Feedback Integral Control (SFIC), and Sliding Mode Control (SMC). A comparative examination of these three controllers has been conducted focusing on identifying the most effective controller for battery-powered EV applications. In the system under consideration, the converter consistently steps down a 12 V input from a fully charged battery to an output of approximately 5 V. The performance of each controller was evaluated through simulations conducted in the MATLAB/Simulink environment, based on the behavior of the Li-ion battery source. The SMC outperformed PI and SFIC in terms of transient response, voltage regulation, and the Integral of Squared Error (ISE). Therefore, SMC was also evaluated under varying battery State of Charge (SoC) levels of 100%, 75%, 50%, and 25%. Comprehensive results demonstrating the effectiveness of these control methods for buck converters in electric vehicles have been presented.